2021
DOI: 10.1007/s00394-021-02497-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high intake of cod or salmon on serum total neopterin concentration: a randomised clinical trial

Abstract: Purpose Primarily, to investigate the effect of high intake of cod (lean fish) or salmon (fatty fish) on serum concentration of total neopterin, a marker of cellular immune activation that is associated with cardiovascular disease. Second, to investigate effects of high cod/salmon intake on antioxidant vitamins and elements essential for activity of antioxidant enzymes. Methods In this randomised clinical trial, 63 participants with overweight/obesity cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Further, adult study participants with overweight/obesity consuming five weekly dinners with cod fillet actually had lower serum concentration of neopterin (stimulated by interferon-γ during immune activation) (50) , with no changes in serum concentrations of TNF-α, IL-8 and monocyte chemoattractant protein 1 (51) .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Further, adult study participants with overweight/obesity consuming five weekly dinners with cod fillet actually had lower serum concentration of neopterin (stimulated by interferon-γ during immune activation) (50) , with no changes in serum concentrations of TNF-α, IL-8 and monocyte chemoattractant protein 1 (51) .…”
Section: Discussionmentioning
confidence: 92%
“…This is also supported by previous observations of no signs of increased inflammation in obese Zucker fa/fa rats after dietary treatment with Atlantic cod (48) or blue whiting ( Micromesistius poutassou ) (49) , both members of the Gadidae family. Further, adult study participants with overweight/obesity consuming five weekly dinners with cod fillet actually had lower serum concentrations of neopterin (stimulated by interferon- γ during immune activation) (50) , with no changes in serum concentrations of TNF- α , IL-8 and monocyte chemoattractant protein 1 (51) .…”
Section: Discussionmentioning
confidence: 99%
“…A randomised cross-over study in overweight men ( n = 32) comparing herring with chicken and pork (750 g/week for 6 weeks) found an increase in s-B12 (8.9%) and s-selenium (4.6%), but not s-vitamin D, during the herring diet [ 5 ]. In the previously mentioned RCT comparing intake of salmon or cod consumed as whole filet (750 g/week), only cod increased s-selenium compared to controls [ 29 ]. We have previously performed a post-prandial analysis of serum amino acids in five healthy adults after intake of the study product, and found a non-significant increase in serum levels of most amino acids [ 15 ], supporting that the capsules were absorbed.…”
Section: Discussionmentioning
confidence: 99%
“…In recent Norwegian studies, median plasma/serum selenium concentrations varied between 64 to 95 µg/L, with 25-percentiles down to 51 µg/L (45)(46)(47)(48). In an earlier study from a clinical chemistry laboratory, serum selenium concentrations were followed from 1995 to 2006.…”
Section: Plasma/serum Concentration Of Seleniummentioning
confidence: 99%